A rapid and precision hot embossing of LGP micro-arch lens array inside core microgrooves: simulation and experiment - Xie, Jin; Jiang, Yuning; Liu, Jinan; Man, Tianrong (International journal of advanced manufacturing technology, 2018)
The hot embossing needs the heat preservation for precision micro-forming, thus leading to inefficiency. A hot embossing of polymer micro-arch lens array in half molten is proposed for the application of light guide plate (LGP). It only performs a thermal deformation for micron-scale surface layer to be squeezed into core microgrooves. First, the micro-optic illumination of LGP was analyzed to design the micro-arch lens array; then the micro-grinding was employed to machine smooth microgrooves on ceramic core die; finally, the hot embossing experiments were conducted to adjust the thermal and structural parameters for modeling micro-arch height. It is shown that the micro-arch lens array may be rapidly and precisely formed inside the core microgrooves in half molten. The micro-arch height reaches 22 μm at a loading time of 5 s. The loading temperature and the core microgroove angle greatly influence the micro-arch height. The parameterized model of micro-arch height and radius may be used to optimize the hot embossing variables and the core microgroove parameters. The LGP patterned with the micro-arch lens array increases the irradiance intensity by 16% and its uniformity by 210% compared with smooth one, respectively.